Electrochemical performance of Na0.6[Li0.2Ni0.2Mn0.6]O2 cathodes with high-working average voltage for Na-ion batteries - de la Llave, Ezequiel Pablo (2017)
Na0.6[Li0.2Ni0.2Mn0.6]O2 is synthesized by a self-combustion reaction (SCR) and studied for the first time as a cathode material for Na-ion batteries. The Na0.6[Li0.2Ni0.2Mn0.6]O2 cathode presents remarkable high rate capability and prolonged stability under galvanostatic cycling. A detailed analysis of X-ray diffraction (XRD) patterns at various states of cycling reveals that the excellent structural stability is due to a primarily solid-solution sodiation/desodiation mechanism of the material during cycling. Moreover, a meaningful comparison with Na0.6MnO2 and Na0.6[Li0.2Mn0.8]O2 reveals that the Na0.6[Li0.2Ni0.2Mn0.6]O2 cathode achieves a very high working-average voltage that outperforms most of the lithium-doped manganese-oxide cathodes published to date.